2017
DOI: 10.1002/stem.2552
|View full text |Cite
|
Sign up to set email alerts
|

A Reinterpretation of Cell Transplantation: GFP Transfer From Donor to Host Photoreceptors

Abstract: The utilization of fluorescent reporter transgenes to discriminate donor versus host cells has been a mainstay of photoreceptor transplantation research, the assumption being that the presence of reporter1 cells in outer nuclear layer (ONL) of transplant recipients represents the integration of donor photoreceptors. We previously reported that GFP 1 cells in the ONL of cone-GFP transplanted retinas exhibited rod-like characteristics, raising the possibility that GFP signal in recipient tissue may not be a cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
119
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(124 citation statements)
references
References 23 publications
3
119
1
Order By: Relevance
“…Our optimized methodology resulted in a high success rate, with 26 out of 29 eyes (89%) supporting the survival of the transplanted cell mass (Figures S6E–S6H), without immune suppression. Reporter-positive photoreceptors were present in the host outer nuclear layer (Figure S6H), but similar to previous studies demonstrated rod-like morphology and were likely the result of uptake of cellular components by host photoreceptors from the subretinal graft (Decembrini et al., 2017, Ortin-Martinez et al., 2016). In the subretinal space, the cells were negative for rod markers RHODOPSIN and GNAT1 (Figures S6E and S6F) and continued to develop in vivo, forming peanut agglutinin (PNA)-labeled extracellular matrix and expressing ARRESTIN3 (Figures S6G and S6H).
Figure 6Isolation and Transplantation of Purified mESC-Derived Cone Precursors(A) Reporter fluorescence driven by AAV2/9-2.1.GFP vector following subretinal injection into adult mouse retina.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our optimized methodology resulted in a high success rate, with 26 out of 29 eyes (89%) supporting the survival of the transplanted cell mass (Figures S6E–S6H), without immune suppression. Reporter-positive photoreceptors were present in the host outer nuclear layer (Figure S6H), but similar to previous studies demonstrated rod-like morphology and were likely the result of uptake of cellular components by host photoreceptors from the subretinal graft (Decembrini et al., 2017, Ortin-Martinez et al., 2016). In the subretinal space, the cells were negative for rod markers RHODOPSIN and GNAT1 (Figures S6E and S6F) and continued to develop in vivo, forming peanut agglutinin (PNA)-labeled extracellular matrix and expressing ARRESTIN3 (Figures S6G and S6H).
Figure 6Isolation and Transplantation of Purified mESC-Derived Cone Precursors(A) Reporter fluorescence driven by AAV2/9-2.1.GFP vector following subretinal injection into adult mouse retina.
…”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, given the advanced degenerative state of the recipient retina, the morphology of transplanted cones was compromised. This contrasts with apparently mature features of GFP-labeled cells observed in cone transplants into non-degenerative retina, which are now understood to arise from cytoplasmic material transfer from the subretinal graft to host rods (Decembrini et al., 2017, Ortin-Martinez et al., 2016). Nonetheless, cones in the Aipl1 − / − recipients appeared to make physical contact with inner retinal neurons and expressed components associated with synaptic transmission, alongside phototransduction-related proteins, suggesting advanced differentiation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Similar mismatch between nuclear morphologies of the grafted cells versus host cells was observed after GFP‐labeled rod precursors were grafted in an S‐cone‐like cell dominated retina ( Nrl ‐/‐). In complementary experiments, they found that transplanting P3–P5 retinal cells isolated from a membrane‐tethered tdTomato mouse line into adult Nrl ‐GFP retinas led to tdTomato+/GFP+ cells in the ONL (Ortin‐Martinez et al, ), similar to what was observed when transplanting GFP+ cells in DsRed retinas. Altogether, these results suggested that some fusion event occurred between the grafted cells and the host photoreceptors.…”
Section: Materials Transfer In the Mouse Retinamentioning
confidence: 65%
“…It is still unclear whether only photoreceptors in the host retina engage in material transfer with the grafted cells. While three groups did not report GFP‐labeled cells outside of the ONL after transplantation of rod precursors (Pearson et al, ; Santos‐Ferreira et al, ; Singh et al, ), another observed low levels of GFP in both bipolar and Müller cells located in the INL (Ortin‐Martinez et al, ). These cells were localized next to areas with high density of material transfer‐labeled host photoreceptors in Nrl ‐/‐ retinas.…”
Section: Materials Transfer In the Mouse Retinamentioning
confidence: 99%
“…E.g., Barnard et al (27) Recently, several laboratories have demonstrated that recipient photoreceptors incorporate GFP label from transplanted photoreceptor precursor cells that were injected into the subretinal space. This means that GFP label alone is insufficient to tell whether donor cells really integrated into the host retina (28)(29)(30). However, Zhu et al showed that GFP-labeled cells stain for human specific markers and do not co-express a mouse-specific MHC class I marker which clearly determined that they were all of human origin.…”
mentioning
confidence: 99%